Is Vasoactive-Inotropic Score a Predictor for Mortality and Morbidity in Patients Undergoing Coronary Artery Bypass Surgery? - Baysal,Pınar Karaca (2021)
Abstract Introduction: We aimed to investigate whether vasoactive-inotropic score (VIS) is a predictor for early postoperative morbidity and mortality. Methods: This study was planned as a prospective cohort study, between Nov 20 2018 and May 15 2019, including a total of 290 patients aged 20 years or older who underwent elective on-pump coronary artery bypass grafting (CABG). Patients’ demographic data, aortic cross-clamp and cardiopulmonary bypass times, European System for Cardiac Operative Risk Evaluation (EuroSCORE) score, cardiac ejection fraction (EF), VIS, intubation duration, and intensive care unit length of stay were recorded. Postoperative mortality and morbidity were recorded. Hourly doses of inotropes for VIS were recorded for each patient, and VIS was calculated. Results: Among the cases, 222 (77%) were male and 68 (23%) were female. The mean age of our patients was 62.5 years (37-86). Combined morbidity and mortality rates of our patients were 23.8%. An optimal cutoff point for VIS of 5.5 could predict combined morbidity and mortality with 90% sensitivity and 88% specificity. Low EF, prolonged operation time, high EuroSCORE, and high VIS are independent factors in the early postoperative period for the development of combined morbidity and mortality in patients who underwent elective CABG. Conclusion: VIS is the most critical and EuroSCORE is the second most important scoring systems. They independently predict combined morbidity and mortality in undergoing elective coronary artery bypass surgery.